Surgical Treatment of Lateral Tibial Plateau Fractures Involving the Posterolateral Column - Shen, Qi‐jie (Orthop Surg, 2019)
OBJECTIVE: To summarize the indications and the clinical effects of a transfibular neck osteotomy approach and a combined anterolateral and posterolateral approach in the treatment of fractures of the lateral tibial plateau involving the posterolateral column. METHODS: Eleven patients with lateral tibial plateau fractures were included in the present study. The fractures were Schatzker type II or lateral platform fractures involving posterolateral column. The anterolateral combined posterolateral approach (lateral + posterolateral locking plate fixation) was applied in 7 patients and 4 patients underwent transfibular neck osteotomy (lateral + posterolateral locking plate fixation + 1/4 tubular plate edge fixation, fibular osteotomy with Kirschner wire tension band fixation, and hollow nail fixation for upper tibiofibular joint). All cases were followed up for 12–24 months, with an average follow‐up of 17.5 ± 5.0 months. At the last followup, the Rasmussen radiological criteria were used to evaluate the effect of fracture reduction and fixation. The knee joint function was evaluated using the knee function evaluation criteria of the Hospital for Special Surgery (HSS). The Lachman test and the pivot‐shift test were used to evaluate the anterior and posterior and rotational stability of the knee joint. The range of knee motion was recorded. RESULTS: Bone healing was achieved in all patients with fractures treated with a transfibular neck osteotomy approach and a combined anterolateral and posterolateral approach. At the last follow‐up, both the Lachman test and the pivot‐shift test results were negative. All patients had complete knee extension. For the combined anterolateral and posterolateral approach, the knee flexion angle was 110°–130°, with an average of 122.86° ± 7.56°. For the transfibular neck osteotomy approach, the knee flexion angle was 115°–130°, with an average of 120.00° ± 7.07°. For the patients in which the combined anterolateral and posterolateral approach was used, the Rasmussen score was 12–18 points, with an average of 16.00 ± 2.56 points. The results were excellent in 4 cases and good in 3 cases; therefore, 100% of results were excellent or good. For patients in which the transfibular neck osteotomy approach was used, the Rasmussen score was 10–18 points, with an average of 15.25 ± 3.77 points. The results were excellent in 2 cases, good in 1 case, and acceptable in 1 case; therefore, 75% of results were excellent or good. The HSS score for the combined anterolateral and posterolateral approach was 76–98 points, with an average of 88.43 ± 7.55 points. The results were excellent in 5 cases and good in 2 cases; therefore, 100% of results were excellent or good. The HSS score for the transfibular neck osteotomy approach was 74–96 points, with an average of 87.25 ± 9.43 points. The results were excellent in 3 cases and good in 1 case; therefore, 100% of results were excellent or good. There were no significant differences in operation time, surgical blood loss, fracture healing time, postoperative imaging score, and knee function evaluation between the two approaches. One patient who underwent transfibular neck osteotomy had a 3‐mm step that gradually appeared, but no significant abnormalities were found in the width of the platform and the lower limb force line. One patient in whom the combined anterolateral and posterolateral approach was used showed numbness in the common peroneal nerve. No common peroneal nerve injury occurred through the transfibular neck osteotomy approach. CONCLUSIONS: The anterolateral combined posterolateral approach and the transfibular neck osteotomy approach are effective in the surgical treatment of lateral tibial plateau fractures involving the posterolateral column. However, the transfibular neck osteotomy approach is more suitable for the posterolateral plateau articular surface damaged with bone separation and displacement, deep collapse, cases involving a large range of the posterolateral column, especially fractures of the lateral tibial plateau in the upper tibiofibular syndesmosis area of the line connecting the anterior and posterior margin of the fibular head to the midpoint of the plateau.